Investigation of Occult Hip Fractures: The Use of CT and MRI. (7th February 2013) - Gill, S. K.; Smith, J.; Fox, R.; Chesser, T. J. S.
Abstract : Aim . At present there is no data looking at modern multislice computerised tomography (CT) in the investigation of occult hip fracture. The aim of this study was to retrospectively compare the reports of patients sent for magnetic resonance imaging (MRI) or CT with negative radiographs and a clinical suspicion of a fractured neck of femur. Methods . All patients presenting to the hospital with a clinical suspicion of a hip fracture but initial negative radiographs over a three-year period were included. Patients were either investigated with an MRI scan or CT scan. The presence of a fracture, the requirement for surgery, and any further requirement for imaging were recorded. Results . Over three years 92 patients were included of which 61 were referred for a CT and 31 for an MRI. Thirty-four patients were found to have a fracture. Of these, MRI picked up a fracture in 36% and CT in 38% of referrals. Discussion . Up to 10% of proximal femur fractures may be missed on initial radiographs. Current guidelines state patients should be offered MRI if hip fracture is suspected despite negative hip radiographs. Our findings show that modern multislice CT may be comparable with MRI for detecting occult fracture.